Capital flight and capital controls in developing countries - Epstein, Gerald A. (Cheltenham, UK ; Northampton, MA : Edward Elgar, 2005)
Using a common methodology for a set of case studies on the size, causes and consequences of capital flight in developing countries, the contributors address the extent of capital flight, its effects, and what can be done to reverse it
Includes bibliographical references and index.
oif 21/08/15
Loan
Keywords: Capital movements